Reading press images, photography and its influence on the intercultural attitude of chilean young people - Aros-Aravena, Alejandro; Esgueva-López, Victoria (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
The image especially influences young people who are more familiar with the various spaces that exhibit them in digital media. For this reason, for the present investigation, the objective of knowing the perception of young university students regarding press images and their impact on their tolerance towards multicultur- alism has been set. A qualitative methodology has been proposed that through the observation of 24 images by 60 students have selected the most satisfactory answer. The conclusions show that the image has a positive impact on interculturality.